Demographic growth and social exclusion in the “peripheral capitals” of the Amazon - Staevie, Pedro Marcelo (Textos e Debates, 2016)
The present article has as main objective to argue the process of demographic growth in the “peripheral capitals” of the Amazonia and its relation with some social indicators. Through the presentation of some indicators on these cities, we intend to demonstrate their socio-economic situation and the necessity of governmental intervention in the combat to the problems reflected in the indicators. Using basically the data presented for Pochmann and Amorim (2004), we search to namely present the social situation of the cities that for the moment we call peripheral capitals of the Amazon: Boa Vista, Macapá, Rio Branco and Porto Velho.